Activation of endothelial NO synthase and P2X7 receptor modification mediates the cholinergic control of ATP-induced interleukin-1β release by mononuclear phagocytes - Richter, Katrin; Asci, Nilay; Singh, Vijay K.; Yakoob, Sanaria Hawro; Meixner, Marion; Zakrzewicz, Anna; Liese, Juliane; Hecker, Andreas; Wilker, Sigrid; Stumpf, Sabine; Schlüter, Klaus-Dieter; Rohde, Marius; et al. (Frontiers in Immunology, 2023)
Objective: The pro-inflammatory cytokine interleukin-1β (IL-1β) plays a central role in host defense against infections. High systemic IL-1β levels, however, promote the pathogenesis of inflammatory disorders. Therefore, mechanisms controlling IL-1β release are of substantial clinical interest. Recently, we identified a cholinergic mechanism inhibiting the ATP-mediated IL-1β release by human monocytes via nicotinic acetylcholine receptor (nAChR) subunits α7, α9 and/or α10. We also discovered novel nAChR agonists that trigger this inhibitory function in monocytic cells without eliciting ionotropic functions at conventional nAChRs. Here, we investigate the ion flux-independent signaling pathway that links nAChR activation to the inhibition of the ATP-sensitive P2X7 receptor (P2X7R). Methods: Different human and murine mononuclear phagocytes were primed with lipopolysaccharide and stimulated with the P2X7R agonist BzATP in the presence or absence of nAChR agonists, endothelial NO synthase (eNOS) inhibitors, and NO donors. IL-1β was measured in cell culture supernatants. Patch-clamp and intracellular Ca2+ imaging experiments were performed on HEK cells overexpressing human P2X7R or P2X7R with point mutations at cysteine residues in the cytoplasmic C-terminal domain. Results: The inhibitory effect of nAChR agonists on the BzATP-induced IL-1β release was reversed in the presence of eNOS inhibitors (L-NIO, L-NAME) as well as in U937 cells after silencing of eNOS expression. In peripheral blood mononuclear leukocytes from eNOS gene-deficient mice, the inhibitory effect of nAChR agonists was absent, suggesting that nAChRs signal via eNOS to inhibit the BzATP-induced IL-1β release. Moreover, NO donors (SNAP, S-nitroso-N-acetyl-DL-penicillamine; SIN-1) inhibited the BzATP-induced IL-1β release by mononuclear phagocytes. The BzATP-induced ionotropic activity of the P2X7R was abolished in the presence of SIN-1 in both, Xenopus laevis oocytes and HEK cells over-expressing the human P2X7R. This inhibitory effect of SIN-1 was absent in HEK cells expressing P2X7R, in which C377 was mutated to alanine, indicating the importance of C377 for the regulation of the P2X7R function by protein modification. Conclusion: We provide first evidence that ion flux-independent, metabotropic signaling of monocytic nAChRs involves eNOS activation and P2X7R modification, resulting in an inhibition of ATP signaling and ATP-mediated IL-1β release. This signaling pathway might be an interesting target for the treatment of inflammatory disorders.